Endothelial Function and Postprandial Glucose Control in Response to Test-Meals Containing Herbs and Spices in Adults With Overweight/Obesity - Huang, Yudai; Tsai, Meng-Fu; Thorat, Rajrajeshwari Sunil; Xiao, Di; Zhang, Xuhuiqun; Sandhu, Amandeep K.; Edirisinghe, Indika; Burton-Freeman, Britt M. (Frontiers in Nutrition, 2022)
Objectives: Herbs and Spices (H/S) contain bioactive compounds with purported health benefits. This study investigated the effect of H/S intake on indicators of vascular and metabolic health over 24 h using a test-meal challenge paradigm in adults with overweight or obesity. Methods: In a randomized, single-blinded, 4-arm, 24 h, multi-sampling, crossover clinical trial, adults (n=25) aged 37±15 years with BMI 28.5±2.8 kg/m2 (mean ± SD) consumed a high-fat, high-carbohydrate challenge meal (~810 kcal) with salt/pepper only (control) or control with one of three different H/S combinations: Italian herb (rosemary, basil, thyme, oregano, and parsley), cinnamon, or pumpkin pie spice mix (cinnamon, ginger, nutmeg, and allspice) on four separate visits at least three days apart. Meals provided 35% of subjects’ energy to maintain weight and ~1 g H/S per 135 kcal of the meal. Flow-mediated dilation (FMD) and blood samples were collected at 0, 1, 2, 4, 5.5, 7, and 24 h for endpoint analysis (additional blood draw at 0.5 h for insulin/glucose). Mixed-model analysis of repeated measures via PROC MIXED PC-SAS 9.4 was performed on the primary outcome (FMD) and secondary outcome variables. This study was registered at ClinicalTrial.gov (NCT03926442). Results: Italian herb and pumpkin spice meals significantly increased %FMD at 24 h compared to the control meal (P = 0.048 and P = 0.027, respectively). The cinnamon meal reduced postprandial glycemia (Δ) compared to control (P = 0.01), and pumpkin pie spice mix and cinnamon meals reduced postprandial insulin at 0.5 h compared to the control meal (P = 0.01 and P = 0.04, respectively). IL-6 and triglycerides increased in response to all meals (Time, P < 0.0001) but were not significantly different between meals. Conclusions: The test-meal challenge study design coupled with multiple sampling over 24 h provides insights into time-course bioactivity of H/S on vascular function and metabolic indices in overweight/obese adults. Funding Sources: McCormick Science Institute